Teaching TCP/IP Networking Using Practical Laboratory Exercises - Sarkar, Nurul I (International journal of information and communication technology education, 2006)
It is often difficult to motivate students to learn TCP/IP networking concepts because students appear to find the subject rather technical, dry, and boring. To overcome this problem, we have prepared some practical laboratory exercises (practicals) and other materials. They are designed around a multi-user, multi-tasking operating system and are suitable for classroom use in undergraduate TCP/IP networking courses. The effectiveness of these practicals has been evaluated both formally by students and informally in discussion within the teaching team. The implementation of the practicals was judged to be successful because of the positive student feedback and because students improved their test results. This article describes the practicals and their impact on student learning and comprehension, based on the author’s experiences in an undergraduate IT course.